Plan de marketing para implementación de restaurante Tex-Mex en Lima - Ponce Puelles, Diego Manuel (2020)
The big offer of restaurants in the city of Lima makes difficult for new brands to position and differentiate from competitors. Therefore, this work seeks to determine the conditions a restaurant should accomplish for being accepted and visited by consumers. In order to determine this conditions, preferences and attitudes were investigated through two focus groups and a preliminary survey with a non-probabilistic sample of two hundred people. Based on the results, a concept was designed and orientated to the customer experience. Pine and Gilmore (1999, 2011) theory of the realms of experience, as well as ISÇI, TÜVER, y GÜZEL (2018) investigation of factors that affect satisfaction and loyalty were used to establish the most relevant conditions for this restaurant. Likewise, it was sought to have a satisfactory experience through all the customer journey presented by Lemon and Verhoef (2016). To verify that the conditions proposed in the design of this concept have a positive impact on the experience perception, the NPS or Net Promoter Scores presented by Reichheld (2003) was used as measurement variable. This indicator was tested trough a survey with a non-probabilistic sample of two hundred people, were the concept was presented and based on it they gave they recommendation rate on a scale of one to ten. Results not only backup the investigation presented by ISÇI, TÜVER, y GÜZEL (2018) determining quality service and esthetics as the most relevant and outstanding factors, they also evidenced that the design and construction of a service through the four realms of experience along the customer journey generates a positive valuation of the experience from the potential customers, leading them to accept and visit a new brand of restaurant, as well as paying a higher price.